Kemampuan Literasi Matematis Siswa MTs Pada Materi Aljabar - WILDAN HAKIM (CONSISTAN (Jurnal Tadris Matematika), 2025)
Mathematical literacy ability is the ability that students have to use mathematics to solve problems in everyday life, including students' ability to understand mathematical concepts, mathematical reasoning, problem solving, mathematical communication and understanding the use of mathematics in everyday life. The aim of this research is to determine the mathematical literacy abilities of class VII students at MTs Darun Najah. The research method used is descriptive qualitative, based on the results of analysis and discussion, viewed from three aspects, namely formulating the situation mathematically, using concepts, facts and mathematical reasons, interpreting, applying and evaluating the results, it can be concluded that at the stage of formulating the mathematical situation the subject has the ability to high mathematical literacy is able to formulate situations mathematically, at the stage of using mathematical concepts, facts and reasons the subject is able to use mathematical concepts, facts and reasons well and at the stage of interpreting, applying and evaluating the results the subject is able to interpret, apply and evaluate the results well. Subjects with moderate mathematical literacy skills are able to formulate situations mathematically, at the stage of using concepts, facts and mathematical reasons the subject is able to use mathematical concepts, facts and reasons well even though the answers given are incomplete and at the stage of interpreting, applying and evaluating the results the subject is unable interpret, apply and evaluate results well. Meanwhile, subjects with low mathematical literacy skills were only able to formulate situations mathematically, for the second and third indicators the subjects were unable to meet the criteria for these indicators.